Sowing times influence canola grain yield and oil quality - Righi (In memoriam), Evandro Zanini; Vazata, Simone; Dalmago, Genei Antonio; Muller, Alexandre Luis; Carvalho, Leticia Zancanaro Giacomini de; Daga, Jacir (Agrometeoros, 2018)
The aim of this study was to evaluate the environmental effect of different sowing times on the productivity and quality of hybrid canola grains Hyola 60, Hyola 61, Hyola 401 and Hyola 432 sown on the dates 05/12/08, 05/31/08, 06/21/08 and 08/02/08, with a sowing test on 04/18/08 with Hyola 401 and Hyola 61 hybrids. The experimental design consisted of randomized blocks in a factorial 4 dates x 4 hybrids. The local environment was characterized by air temperature, relative humidity and rainfall. With these data, we computed the actual (ETR) and reference (ETo) evapotranspiration. The effect of the soil moisture was evaluated with regards to ETR ETo-1. The results were submitted to analysis of variance and the Tukey test at 5% significance for comparison of means. The environmental effect was evaluated by regression analysis. The hybrid Hyola 401 had better productivity while Hyola 60 showed the lowest productivity. The hybrid Hyola 401 presented the best quality indicators. There was a trend of reduction in grain productivity and quality with delayed sowing. The mean air temperature was found to be the main environmental factor affecting yield and quality, particularly in the filling-maturity of grains in the sub-period and throughout the cycle, with reduced production at higher air temperatures.